METHODS OF FORMING PEDAGOGICAL DISCIPLINE IN THE PROFESSIONAL ACTIVITY OF A PRIMARY TEACHER (Universal International Scientific Journal, 2026)
This article highlights the content and importance of developing pedagogical competence, which is important in the professional activities of primary school teachers, as well as innovative approaches, psychological and pedagogical factors, and practical recommendations that serve to develop pedagogical competence.
Keywords: primary education, pedagogical skills, pedagogical tact, pedagogical communication, pedagogical culture, pedagogical ethics, professional reflection, professional competence, pedagogical technology.